1952
DOI: 10.1128/jb.63.4.429-435.1952
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxidative Rancidity in Unsaturated Fatty Acids on the Germination of Bacterial Spores

Abstract: It has been reported that some lots of commercial media contain substances that inhibit germination of anaerobic spores which can be overcome by adding starch (Foster and Wynne, 1948a). Foster and Wynne ascribed this activity to the unsaturated C18 fatty acids. Halvorson (1950) suggested that this effect may be due to the formation of peroxides from the fatty acids. This investigation was undertaken to test the latter hypothesis. MATERIALS AND METHODS Organisms used. The routine test organism was a putrefactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

1954
1954
1980
1980

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 3 publications
1
9
1
Order By: Relevance
“…The effectiveness of fatty acids varied in suppressing germination of C. botulinum spores in two different lots of the same medium. In contrast to the above findings, Roth and Halvorson (1952) reported that as much as 1.0 per cent of nonrancid methyl esters of oleic, linoleic, and linolenic acids were noninhibitory to spores of C. botulinum, whereas oxidized samples of all 3 acids caused significant inhibition at 0.01 per cent concentrations.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The effectiveness of fatty acids varied in suppressing germination of C. botulinum spores in two different lots of the same medium. In contrast to the above findings, Roth and Halvorson (1952) reported that as much as 1.0 per cent of nonrancid methyl esters of oleic, linoleic, and linolenic acids were noninhibitory to spores of C. botulinum, whereas oxidized samples of all 3 acids caused significant inhibition at 0.01 per cent concentrations.…”
Section: Discussioncontrasting
confidence: 61%
“…This fact suggested that the observed inhibition of C. botulinum may be due to an accumulation of free fatty acids in the cheese during prolonged storage. Fatty acids were reported to inhibit germination of spores of C. botulinum (Humfeld, 1947;Foster and Wynne, 1948); subsequently other authors stated that oxidative rancidity of the fatty acids was the cause of the observed inhibition (Roth and Halvorson, 1952). The amount of free fatty acids formed during aging of cheese varies (Van Slyke and Price, 1952), and factors affecting the rate of fatty acid formation are little known (Babel and Hammer, 1945).…”
mentioning
confidence: 99%
“…I n a comparative study of media for counting Clostridiuln spores, it was reported by Wynne and Foster ( 5 ) that a modified Yesair's pork infusion agar with added soluble starch yielded the highest counts. Although this medium has been used routinely in our laboratory and elsewhere (2, 4 ) , it is expensive and difficult to prepare. The present investigation concerns a yeast extract medium offered as a possible replacement for the pork infusion and other complex media currently used for counting spores.…”
mentioning
confidence: 99%
“…Foster & Wynne (1948) reported that some batches of media contain substances that inhibit the germination of anaerobic spores and ascribed it to the presence of unsaturated C,, fatty acids. Halvorson (1950) and Roth & Halvorson (1952) ascribed the inhibitory effects to organic peroxides, the latter authors suggesting that hydrogen peroxide produced temporarily might be the factor involved.…”
Section: Discussionmentioning
confidence: 99%